Opioid-induced constipation in adult oncology patients - Dias, Daniela (2017)
Opioids are gold-standard for the treatment of cancer pain, but some of its adverse effects may compromise its therapeutic potential, such as constipation. This change in elimination pattern is characterized by reduced bowel movements, increased effort in bowel movements, incomplete rectal evacuation sensation, or hard stool consistency. The prevention and treatment of constipation requires a rigorous assessment, mainly in patients at risk and a complete understanding of its aetiology. The assessment requires data collection patient’s clinical history, focusing on the level of physical activity, eating habits, chewing and swallowing ability, underlying medical problems and changes in bowel habits and stool characteristics. It also requires an accurate physical examination (oral cavity, abdominal region and anorectal). In the presence of opioid-induced constipation, pharmacological measures (with laxative effect and /or inhibitors of intestinal opioid receptors, without loss of analgesic efficacy and opioid rotation) and non-pharmacological measures (food hygiene measures, bowel education and abdominal massage). In this article we intend to make a theoretical framework of OIO and present prevention and control measures aimed at improving the care provided by nurses and consequently a better quality of life for those we care for.